2021
DOI: 10.3390/admsci11030088
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Economic Dynamics and Female Entrepreneurship: Reflections for the Visegrad Countries

Abstract: The gender gap in entrepreneurship has been observed for a long time, explained by both female-specific and gender-neutral factors, but none of these explanations is generally accepted. The aim of the paper is to assess the effect of internal economic dynamics on female entrepreneurship. Economic dynamics is a persistent process affected simultaneously by both endogenous and exogenous factors of a different time horizon, with the development trend and the business cycle as the most important time perspectives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Thus, the effects of sex-related values, attitudes, and ethical tendencies (e.g., benevolence and universalism) warrant consideration (Eagly et al 2014). The mainstream business literature has shown that firms set up and run by females exhibit a set of distinctive features (Bruni et al 2004;Paoloni 2021;Gawel and Głodowska 2021;Knowles and Mainiero 2021). Some scholars increasingly assert that females have an advantage in leadership, whereby women are more likely than men to lead in a style that is effective under the current conditions.…”
Section: The Factors Influencing a Firm's Value During A Crisis: Relational Capital Other Intangibles And Female Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effects of sex-related values, attitudes, and ethical tendencies (e.g., benevolence and universalism) warrant consideration (Eagly et al 2014). The mainstream business literature has shown that firms set up and run by females exhibit a set of distinctive features (Bruni et al 2004;Paoloni 2021;Gawel and Głodowska 2021;Knowles and Mainiero 2021). Some scholars increasingly assert that females have an advantage in leadership, whereby women are more likely than men to lead in a style that is effective under the current conditions.…”
Section: The Factors Influencing a Firm's Value During A Crisis: Relational Capital Other Intangibles And Female Capabilitiesmentioning
confidence: 99%
“…In this changed environmental context, investigating women managers' contribution to the productive world has become central to gender equality because investment in women boosts economic development, competitiveness, job creation, and G.D.P. (Gawel and Głodowska 2021;Marlow and McAdam 2013). The OECD estimates that, on average, across the OECD, a 50% reduction in the gender gap in labor force participation would lead to an additional gain in G.D.P.…”
Section: The Factors Influencing a Firm's Value During A Crisis: Relational Capital Other Intangibles And Female Capabilitiesmentioning
confidence: 99%
“…Bellò et al (2018) proved empirically the relations between creativity and entrepreneurial intentions, and what is more the entrepreneurial self-efficacy mediates the relationship between creativity and entrepreneurial intentions (based on a sample of 507 students from Italy). Similarily, Smith et al (2016) empirically confirmed that creativity has a direct and positive effect on entrepreneurial intentions, and additionally creativity had a stronger relationship with intentions among women as female entrepreneurship is still an unexplored research domain (Gawel & Głodowska, 2021). Wang et al (2022) supported also the other side relation that entrepreneurial education enhances individual creativity of students as well as creativity in university.…”
Section: Empirical Findings and Discussionmentioning
confidence: 56%
“…Recently, there have been studies in different Eastern European countries on entrepreneurship as follows: Gawel and Głodowska (2021), who investigated the effect of economic dynamics on female entrepreneurship in the Visegrad countries, specifically Czechia, Hungary, Poland, and Slovakia. The study revealed that economic dynamics impact female entrepreneurship to an extent, but in a less important way.…”
Section: Discussionmentioning
confidence: 99%